Light induced grafting-from strategies as powerfull tool for surface modification - M. Sangermano; N. Razza (eXPRESS Polymer Letters, 2019)
Chemical-induced grafting processes can be performed either a grafting-to method, where preformed polymer chains are grafted on the surface previously activated, or alternatively, the polymer chains can be grown from the surface via a grafting-from method. The last one can be considered a bottom-up approach in which polymers are generated directly on the surface starting from their precursors. As a preliminary process the substrate is functionalized with specific groups that can initiate a polymerization reaction. While the polymerization can be initiated by a thermal initiator or directly by radicals formed by high energy treatment of the surface, light induced triggering of the grafting reaction has recently found increasing interest. With this review, by placing emphasis on the initiating system, we aim to show the significant feasibility of photografting-from method to properly functionalize any type of surface.